Efecto de los parámetros óptimos de combustión de la antracita aglomerada con arcilla y cal en el incremento de la eficiencia y disminución de efluentes sulfurosos - Seijas Velásquez, Segundo (2007)
In this work the effect of the optimization of the parameters excess of air and combustion intensity of the anthracite amassed with clay and lime in the increment of the efficiency and flue-gas desulfurization has been determined; for that which a chamber of stationary combustion of laboratory was used and for the rehearsals pilot a boiler of 80 BHP making matter balances and energy evaluating the combustion gases for each level of process variables. In the process of determination the most significant variables, it was followed the model of Plackett and Burman and for their optimization the Patron Yates , for values of excess of air in the range of 5,5 to 17% (in weight) and combustion intensities, between 900 and 1800 MJ/hm³. The maximum efficiency of the combustion chamber was of 81, 20% for an excess of air of 6, 0%, and combustion intensity of 1150 MJ. /h.m³ and 72% of sulfur gases was removed using 1,5% of CaO. The equations using for the optimum scaling of a boiler to coal in function of the combustion parameters are: Flow of combustion gases: (m³/min.) θg = 0,4518 * BHP Power of the fan induced shot: (HP) HPg = 0,0307 * BHP Chamber volume (stationary): (m³) Vca = 0,045* BHP Traverse surface of the chimney: (m²) Ach = 0,0012 * BHP Power of the fan induced shot: (HP) HPg = 0,0307 * BHP